Notes on the Chapel Yard, Inverness, and some of its Old Monuments, with a notice of Heraldic Devices on Tombstones at Kilmun (Proceedings of the Society of Antiquaries of Scotland, 1911)
The Chapel Yard of Inverness is one of three old burying-grounds which are occasionally still used for burial. Documentary references to the old churches of Inverness are considered as is the likely date of the Chapel Yard. The first actual reference by name to the Parish Church of Inverness is in a charter by Alexander in 1240 in which a grant of land is given to the order of Black Friars. The relationship of minor chapels, chaplaincies and alterages to the churches is discussed. The earliest surviving memorial in the burial ground is a recumbent slab which bears the date 1604. There are numerous stones of early eighteenth-century\r work bearing the well-known symbols of the skull, cross-bones, crossspades, coffin, hour-glass, and bell; the not uncommon arrangement of a central heart flanked by initials and surmounted by a date; a few trade symbols such as the tailor's goose and scissors and the smith's hammer and anvil; a crown with crossed sword and scabbard; crude spelling and lettering, and the invariable legend memento mori. There are also numerous examples of heraldic work. Kilmun is situated on the north shore of the Holy Loch and was the burial place of the Argyll family. Little can be said of the stones other than the fact that they display 'faked ' heraldic designs.